ANALYSING THE EFFECT OF HUMAN RESOURCE POLICIES ON MACROECONOMIC INDICATORS - Loso Judijanto; Sherly Etika Sari; Al-Amin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This analysis explores the impact of Human Resource (HR) policies on macroeconomic indicators. The findings show that well-planned HR policies can influence economic growth through improving labour skills, productivity, and reducing unemployment rates. Policies that focus on education, training, and employee retention play an important role in improving national productivity and the quality of life of the workforce. In addition, attention to employee welfare and diversification of the workforce through gender inclusion and equality can encourage wider participation in the labour market. Thus, effective and inclusive HR policies not only enhance the competitiveness of companies but also support sustainable economic growth and the overall well-being of society.